Assessing the implications of allowing transgender personnel to serve openly - Schaefer, Agnes Gereben (Research report (Rand Corporation), 2016)
"Recent U.S. Department of Defense (DoD) policy banned transgender personnel from serving openly in the military. Potential changes to this policy raised questions regarding access to gender transition--related health care, the range of transition-related treatments that DoD will need to provide, the potential costs associated with these treatments, and the impact of these health care needs on force readiness and the deployability of transgender service members. A RAND study identified the health care needs of the transgender population and transgender service members in particular. It also examined the costs of covering transition-related treatments, assessed the potential readiness implications of a policy change, and reviewed the experiences of foreign militaries that permit transgender personnel to serve openly"--Publisher's description